2015
DOI: 10.1137/140974407
|View full text |Cite
|
Sign up to set email alerts
|

Solution of Nonlinear Stokes Equations Discretized By High-Order Finite Elements on Nonconforming and Anisotropic Meshes, with Application to Ice Sheet Dynamics

Abstract: Abstract. Motivated by the need for efficient and accurate simulation of the dynamics of the polar ice sheets, we design high-order finite element discretizations and scalable solvers for the solution of nonlinear incompressible Stokes equations. In particular, we focus on power-law, shear thinning rheologies commonly used in modeling ice dynamics and other geophysical flows. We use nonconforming hexahedral meshes and the conforming inf-sup stable finite element velocity-pressure pairings, where k ≥ 2 is the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 57 publications
0
69
0
Order By: Relevance
“…For this process to be computationally tractable during both the inverse (parameter estimation and uncertainty assignment) and forward propagation steps, it is crucial to have robust, efficient, and scalable solves on HPC platforms (Isaac et al, 2014). This, in turn, requires advanced dynamical core capabilities, such as access to model derivatives (e.g., the Jacobian matrix), and advanced algorithms for the solution of the nonlinear and linear equations.…”
Section: K Tezaur Et Al: a Finite Element First-order Stokes Apmentioning
confidence: 99%
See 2 more Smart Citations
“…For this process to be computationally tractable during both the inverse (parameter estimation and uncertainty assignment) and forward propagation steps, it is crucial to have robust, efficient, and scalable solves on HPC platforms (Isaac et al, 2014). This, in turn, requires advanced dynamical core capabilities, such as access to model derivatives (e.g., the Jacobian matrix), and advanced algorithms for the solution of the nonlinear and linear equations.…”
Section: K Tezaur Et Al: a Finite Element First-order Stokes Apmentioning
confidence: 99%
“…Oscillatory components are effectively reduced through a simple iterative procedure, while smooth components are tackled using auxiliary lower-resolution versions of the problem. Different geometric multigrid methods have been successfully applied to the linear systems arising from ice sheet modeling simulations, e.g., Brown et al (2013); Cornford et al (2013); Isaac et al (2014).…”
Section: Multilevel Preconditioningmentioning
confidence: 99%
See 1 more Smart Citation
“…high aspect ratio elements, see Chapter 7 [28]). Such an approach was advocated in [6,12], where ICC(0) with a column-oriented (e.g. perpendicular to the anisotropy) ordering of the unknowns provides an exact column solve and thus is a highly efficient smoother.…”
Section: Example Use Casesmentioning
confidence: 99%
“…The finite-element discretization of the full Stokes model leads to a well-studied saddle point problem, which represents an active area of research in geophysics (e.g., Benzi et al, 2005;Elman et al, 2014). While recent work (e.g., Isaac et al, 2015) has shown promising results, stable iterative full Stokes solvers are not readily available and, in general, are significantly disruptive to integrate in terms of their code base, which is the reason we will not be considering them in this study.…”
Section: Introductionmentioning
confidence: 99%